The Current Status of Cooperation between Companies and Vocational Schools in the German Dual Apprenticeship System: The Perspective of the Companies - Gessler, Michael [Verfasser] (My University, 2017)
"The principle of duality of the two learning locations - company and school - forms the birth of the term "Dual System" in 1960s. It is a system of simultaneous training in companies and vocational schools. Dual and the interaction of the learning locations characterize the original concept. Empirical studies in the past showed, that the interaction is week. It seems that the duality is more pronounced than the interaction. But, there are gaps in the data: The most recent differentiated survey of companies are from 2008. It is unclear how companies evaluate cooperation between learning locations today. The research question of the study is: How do experts for in-company training in companies (such as trainers, instructors, HRM) evaluate cooperation between the two learning locations, company and school, and what measures are considered important to intensify cooperation between the two learning locations? In the presentation actual data from an empirical survey in the city state Bremen are presented and discussed." (author's abstract; BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 3.1 Berufsbildende Schulen; S 3.2 Unternehmen und Behörden; S 2.4.1 Lernortkooperation; Duales System; Berufsausbildung; Lernort Schule; Lernort Betrieb; Lernortkooperation; Evaluation; Bremen